Usability Evaluation of E-Commerce Website - Madiha Qadir; Adnan Ali (Garuda Prestasi Nusantara Consulting, 2021)
Shopping is one of the fundamental part in our everyday life. These days, individual’s way of life is extraordinary. Individuals feel awkward and set aside a long effort to go to swarmed markets. So e-shopping is a gift as it spares a ton of time. Online buys are a procedure by which shoppers purchase merchandise straightforwardly to a dealer without a web business administration. Purchasers can visit online stores from the online websites. Online stores are accessible twenty-four hours per day and mostly buyers have internet get to both at work and at home. So it is helpful for them to purchase on the web. We have to know the blemishes of interface which client confronted. Compelling plan of interface increment trust of clients. This study endeavours the convenience assessment of homeshopping.pk sites. In this study used user testing and questionnaire which is best strategy.